The bidirectional relationship between destructive leadership and organizational commitment - Elgueta, Jorge A.; Grill, Martin (Frontiers in Psychology, 2025)
IntroductionThis study aimed to determine how destructive leadership and organizational commitment relate to each other across time.MethodsOver 18 months, a self-rated questionnaire was distributed at four timepoints to employees of local government organizations in a municipality in Sweden; 582 employees responded to the questionnaire on at least one occasion. The Destructive Leadership Scale was used to measure destructive leadership, and the Commitment to the Workplace scale was used to measure organizational commitment. A second-order parallel-process latent growth curve model was used to test if initial levels of destructive leadership predict later change in organizational commitment, if initial levels of organizational commitment predict later change in destructive leadership, and if changes in destructive leadership are associated with simultaneous changes in organizational commitment.ResultsThe results show that the initial levels of destructive leadership negatively predicted change in organizational commitment (β = −0.66, p < 0.001), the initial levels of organizational commitment negatively predicted change in destructive leadership (β = −0.84, p < 0.002), and the rate of change in destructive leadership was strongly and negatively associated with the rate of change in organizational commitment (r = −0.96, p < 0.001).DiscussionThe findings indicate that destructive leadership affects the work environment in a negative way by undermining employee’s organizational commitment. At the same time, managers are negatively affected by uncommitted employees, exacerbating destructive leadership behaviors.